What is The Relationship Between Seasonal Weather Variations and Tension Headache Prevalence among Working Professionals in Urban Environments? : A Systematic Review - Satya Agung Nugroho; Nazalla Gwen Vaganesha; Hasnan Habib Afifudin (The Indonesian Journal of General Medicine, 2025)
Introduction: Tension-type headaches are a prevalent condition among working professionals in urban environments, significantly impacting productivity and quality of life. While anecdotal evidence suggests a link between weather changes and headache onset, scientific validation for this association remains unclear. This systematic review aims to evaluate the relationship between seasonal weather variations and the prevalence of tension-type headaches among this specific population. Methods: Following the PRISMA 2020 guidelines, a systematic search was conducted across PubMed, Semantic Scholar, Springer, and Google Scholar. The review included observational studies, cohort studies, case-control studies, and systematic reviews focusing on adult working professionals (18-65 years) in urban settings who experience tension-type headaches. The primary criteria required studies to have clear methodologies for measuring outdoor weather variables. Results: The search identified 10,306 records, from which 21 studies were included in the final synthesis. A significant finding was the profound lack of direct evidence; the majority of included studies did not measure or report on weather variables. The few that did found associations between barometric pressure changes and self-reported weather sensitivity with headache induction. In contrast, the review found substantial evidence linking workplace factors to headaches, including sedentary work, indoor air quality, and psychological stress. Interventions such as acupuncture and relaxation exercises were shown to be effective in reducing headache frequency and severity. Discussion: The scarcity of high-quality research prevents a definitive conclusion on the relationship between seasonal weather and tension headaches. The available evidence is more robust in identifying modifiable occupational and indoor environmental risk factors. The findings suggest that for urban professionals, the immediate work environment may be a more significant and consistent contributor to headache pathogenesis than ambient meteorological conditions. Conclusion: While the link between seasonal weather and tension headaches in urban working professionals remains unverified due to a lack of dedicated research, this review highlights the critical role of the workplace environment. Addressing occupational risk factors through targeted interventions presents a more evidence-based approach to mitigating the burden of tension headaches in this population.